2022
DOI: 10.1002/pc.26648
|View full text |Cite
|
Sign up to set email alerts
|

Review of curing deformation control methods for carbon fiber reinforced resin composites

Abstract: Under the influence of extrinsic curing conditions and intrinsic properties of carbon fiber reinforced resin composites, the formation of curing deformation is inevitable, which makes the shape of the manufactured components differ from the designed structure, and even exceeds the assembly tolerance, resulting in the scrap of parts. Therefore, it is very urgent and important to optimize the curing deformation of carbon fiber reinforced resin composites. In this paper, the mechanism of stress and curing deforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 129 publications
0
10
0
Order By: Relevance
“…The shape of the components has an important influence on the distribution of temperature and curing degree. 9 Zhang et al 17 proposed that the curing process of complex components should be optimized to reduce curing deformation. They also proposed a formula to calculate the curing heating temperature, but the calculation is complex and inefficient.…”
Section: Introductionmentioning
confidence: 99%
“…The shape of the components has an important influence on the distribution of temperature and curing degree. 9 Zhang et al 17 proposed that the curing process of complex components should be optimized to reduce curing deformation. They also proposed a formula to calculate the curing heating temperature, but the calculation is complex and inefficient.…”
Section: Introductionmentioning
confidence: 99%
“…FBG sensors have an immense potential to monitor the curing process and residual stress measurement due to the shrinkage of epoxy resin. [4][5][6][7][8] Dunphy et al [9] and Murukeshan et al [10] utilized the FBG sensors for cure monitoring, where the change in the center wavelength of the FBG sensor is tracked to both monitors the vitrification and curing of thermoset composite. K Jung et al [11] embedded an FBG sensor into the 3-D hybrid braided composite tube.…”
Section: Introductionmentioning
confidence: 99%
“…Shah et al 9 studied the spring‐in phenomenon of antenna reflector through experimental methods, and the results showed that the mold material had a significant impact on the spring‐in values for composite parts. In addition, Zhang et al 10 also reviewed that the stretching effect of the mold surface on the fabricated part is an important factor affecting the warpage of the plate in the curing process. And Galinska et al 11 believed that if the tool is not manufactured from the carbon–epoxy composite material, its thermal expansion is a significant factor that causes additional deformations.…”
Section: Introductionmentioning
confidence: 99%